2013
DOI: 10.1128/aac.02353-12
|View full text |Cite
|
Sign up to set email alerts
|

Polymyxin Resistance of Pseudomonas aeruginosa phoQ Mutants Is Dependent on Additional Two-Component Regulatory Systems

Abstract: e Pseudomonas aeruginosa can develop resistance to polymyxin as a consequence of mutations in the PhoPQ regulatory system, mediated by covalent lipid A modification. Transposon mutagenesis of a polymyxin-resistant phoQ mutant defined 41 novel loci required for resistance, including two regulatory systems, ColRS and CprRS. Deletion of the colRS genes, individually or in tandem, abrogated the polymyxin resistance of a ⌬phoQ mutant, as did individual or tandem deletion of cprRS. Individual deletion of colR or col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
82
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(85 citation statements)
references
References 73 publications
1
82
0
2
Order By: Relevance
“…A third regulator, ParRS, has also been shown to be involved in adaptive resistance to polymyxins (18). More recently, two additional regulators (ColRS and CprRS) that are essential for PhoPQmediated peptide resistance have been identified (20,25). Adding to the complexity, ColRS and CprRS also appear to regulate polymyxin resistance outside of 4-amino-L-arabinose modification of lipid A.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A third regulator, ParRS, has also been shown to be involved in adaptive resistance to polymyxins (18). More recently, two additional regulators (ColRS and CprRS) that are essential for PhoPQmediated peptide resistance have been identified (20,25). Adding to the complexity, ColRS and CprRS also appear to regulate polymyxin resistance outside of 4-amino-L-arabinose modification of lipid A.…”
Section: Discussionmentioning
confidence: 99%
“…Several two-component regulatory systems that control expression of the arn operon have been identified. Under the pressure of low-Mg conditions (19) or exposure to polymyxins (12,18,20,21), PhoPQ has been demonstrated to regulate expression of the arn operon. Similarly, PmrAB can also affect expression of the arn operon under low-cation conditions (22) or following exposure to polymyxins (12,18,22,23).…”
Section: Discussionmentioning
confidence: 99%
“…Its expression is regulated by at least four two-component regulatory systems (PmrAB, PhoPQ, ParRS, and CprRS) (45,46). Since mutations in the genes phoQ, pmrB, parS, parR, colS, cprS, and cprR were previously identified to contribute to polymyxin resistance in P. aeruginosa clinical strains, we amplified and sequenced them in the four CF clinical strains selected (45)(46)(47). Sequences analysis (Table 2) revealed that all the strains harbored the amino acid substitution Tyr345His in the PmrB protein, which was also identified in many susceptible strains, such as strains PA14, PACS2 2192, and C3719.…”
Section: Resultsmentioning
confidence: 99%
“…Mutations in this system cause constitutive expression of the pmrHFIJKLM operon and thus lead to the addition of L-Ara4N to the LPS, leading to colistin resistance. Additionally, mutations in the ColRS and CprRS two-component regulatory systems may also contribute to polymyxin resistance, since the association of mutations in the phoQ gene and mutations in the colS or cprS gene confers a high level of colistin resistance (172). The action of the ColRS and CprRS systems may occur through the activation of the phoQ gene and/or through other genes that have not yet been identified.…”
Section: Mechanisms Of Polymyxin Resistance In Pseudomonas Aeruginosamentioning
confidence: 99%